Direct bonded fixed partial denture with an artificial denture tooth as a pontic - Naomi Tanoue; Yoshimasa Takeuchi; Mika Furuchi; Tetsuo Yamamori; Shuji Ohkawa (Elsevier, 2021)
Background: The present review aimed to investigate the feasibility and clinical effectiveness of a direct bonded fixed partial denture (DBFPD) based on available literature. The efficiency of a DBFPD is mainly affected by the type of artificial denture tooth, the type of luting agent, and the adhesive preparation. Methods: The parameters were reviewed based on the in vitro and in vivo studies conducted. An acrylic resin tooth or a composite resin tooth for removable dentures should be used as the artificial tooth for the pontic. Results: Considering the luting agent, a methyl methacrylate-based resin luting agent, which has low mechanical strength but is capable of plastic deformation and could sustain for a long time, should be used. Appropriate pre-adhesive treatment should be performed on both the artificial and abutment teeth. The cases in which a DBFPD can be applied are limited to one missing anterior tooth, as long as it is not overstressed. Patient cooperation in cases of occlusion seems to be another prerequisite. Conclusion: Knowledge and selection of the material and case indications are essential, and patient cooperation is pertinent in studying the long-term prognosis of a DBFPD.